Impact of EMU on selected non-European-Union countries - Feldman, Robert A. (Washington, DC : International Monetary Fund, 1998)
This Occasional Paper presents three papers in one volume Chapter 1 provides an analysis of the likely impact of EMU on three regions: Central and Eastern Europe, the Mediterranean Basin, and the African CFA zone. Chapter 2 focuses on the trade and financial effects of EMU on selected transition and Mediterranean countries. And Chapter 3 considers the possible implications of EMU for the Middle East and North Africa region.
Includes bibliographical references.
lje 21/07/16
Loan
Keywords: Monetary unions; Monetary policy; European Union countries